2010
DOI: 10.1186/1471-2180-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Identification of possible targets of the Aspergillus fumigatus CRZ1 homologue, CrzA

Abstract: BackgroundCalcineurin, a serine/threonine-specific protein phosphatase, plays an important role in the control of cell morphology and virulence in fungi. Calcineurin regulates localization and activity of a transcription factor called CRZ1. Recently, we characterize Aspergillus fumigatus CRZ1 homologue, AfCrzA. Here, we investigate which pathways are influenced by A. fumigatus AfCrzA during a short pulse of calcium by comparatively determining the transcriptional profile of A. fumigatus wild type and ΔAfcrzA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 58 publications
(81 reference statements)
3
64
0
Order By: Relevance
“…[14][15][16][17][18][19][20] The zinc finger transcription factor Crz1 is the molecular target of calcineurin, that mediates nuclear translocation of Crz1 after dephosphorylation. 19 Orthologs of S. cerevisiae Crz1 are involved in virulence and pathogenesis in several plant and human fungal pathogens, such as Magnaporthe oryzae, Botrytis cinerea, A. fumigatus and Candida glabrata.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…[14][15][16][17][18][19][20] The zinc finger transcription factor Crz1 is the molecular target of calcineurin, that mediates nuclear translocation of Crz1 after dephosphorylation. 19 Orthologs of S. cerevisiae Crz1 are involved in virulence and pathogenesis in several plant and human fungal pathogens, such as Magnaporthe oryzae, Botrytis cinerea, A. fumigatus and Candida glabrata.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Interestingly, it has been shown that calcineurin regulates the transcription of chitin synthases in response to caspofungin treatment in A. fumigatus (62). However, CrzA seems to play only a minor role in this process: in the transcriptional profiles, only chitin synthase A (chsA) was misregulated in response to Ca 2ϩ treatment (61). Additionally, Cramer et al showed that calcineurin but not CrzA is involved in the regulation of ␤-1,3-glucan biosynthesis genes in A. fumigatus (18).…”
Section: Genes Regulated By Crz1mentioning
confidence: 99%
“…Transcriptional profiling of a ⌬crz1 strain in Cryptococcus neoformans under conditions of nutrient limitation revealed 208 downregulated genes compared to the wild type (60). In Aspergillus nidulans, 25 genes were induced under calcium stress conditions in a ⌬crzA strain (24), and in A. fumigatus, Soriani et al identified between 400 and 3,200 genes (depending on the length of the Ca 2ϩ pulse) whose expression is CrzA dependent (61). In both Aspergillus studies, putative CDREs were identified in the promoter regions of CrzA-dependent genes.…”
Section: Genes Regulated By Crz1mentioning
confidence: 99%
“…Upon activation by increased Ca 2+ in the cytosol, CN dephosphorylates Crz1 and the dephosphorylated Crz1 is then transferred to the nucleus from the cytosol for the regulation of target gene expression (Santos and de Larrinoa 2005;Soriani et al 2008;Kim et al 2010). In A. fumigatus, a Crzl homologue was shown to activate many stress-responsive genes, such as those encoding class V chitinase, multidrug-resistance proteins and heat-shock protein Scf1, at increased Ca 2+ levels (Soriani et al 2010). Deletion of the Crz1 gene in Magnaporthe oryzae caused phenotypic changes in vegetative growth, sporulation, conidial viability, pathogenicity and stress tolerance (Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%